Predictive value of [68Ga]Ga-FAPI-04 PET/CT on pathologic response to neoadjuvant chemoimmunotherapy for locally advanced resectable oral squamous cell carcinoma. - Jiang, Yaqun; Yu, Zili; Sun, Yanan; Tian, Yueli; Wang, Li; Xing, Diankui; Huang, Yiwei; He, Yong; Jia, Jun (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: This prospective study aimed to investigate the performance of [68Ga]Ga-FAPI-04 PET/CT for prediction of pathologic response to neoadjuvant chemoimmunotherapy (NACI) in patients with resectable locally advanced oral squamous cell carcinoma (LAOSCC). Methods: Thirty-one treatment-naïve OSCC patients (stage III–IVA) scheduled to receive two cycles of NACI followed by radical surgery were enrolled. [68Ga]Ga-FAPI-04 PET/CT was performed at baseline and after the second cycle of NACI. Semiquantitative PET parameters of the primary tumor were recorded or calculated, namely SUVmax, SUVmean, SUVpeak, and their change rates (∆SUVs, %). PET parameters were compared between the two groups, and their correlation with pathologic response, PD-L1, fibroblast activation protein (FAP), granzyme B (GZMB) expression, and infiltration of CD8+ T lymphocytes in the tumor tissues was also analyzed. Results: Twenty patients were included in the final analysis. Eight patients (40.0%) achieved major pathological response (MPR), including 6 with pathologic complete response (pCR), while 12 patients (60.0%) were categorized as non-MPR according to postoperative histopathological findings. The average preoperative SUVmax was significantly lower in the MPR group (9.38 ± 2.60) compared with that in the non-MPR group (16.20 ± 5.23; P = 0.003), while baseline SUVmax was not significantly different (P = 0.053). The ∆SUVmax (%) in the MPR group (− 59.10% ± 13.33) was notably lower than that in the non-MPR group (− 15.96%, [− 52.56%, 66.33%]; P = 0.002). Preoperative SUVs and ∆SUVs were significantly associated with pathologic response. FAP expression was positively correlated with preoperative SUVs, and the MPR group showed higher CD8 and GZMB expression versus the non-MPR group. Conclusion: [68Ga]Ga-FAPI-04 PET/CT parameters are able to well predict the achievement of MPR following NACI in patients with LAOSCC. ΔSUVs are identified as significant predictors of MPR. These findings warrant validation in larger cohorts. Clinical trial registration: This prospective study was reviewed and approved by the Medical Ethics Committee of Zhongnan Hospital, Wuhan University, and was registered online at NIH ClinicalTrials.gov (NCT05034146 & NCT05030597).